Financial organization and operations of the IMF - International Monetary Fund; Morrison, J.R. (editor); International Monetary Fund (Washington, D.C. : International Monetary Fund, 1998)
This edition attempts to provide a snapshot of the IMF's financial organization as of June 1998. It also describes the Fourth Amendment of the Articles of Agreement, approved by the Board of Governors in September 1997.
Includes glossary.
rpm 30/08/16
Loans
Keywords: International Monetary Fund; Financial organisation; IMF operations